Clinicopathological patterns of benign and malignant sino-nasal tumours: insights from a single-center study - Haque, Muhammad Mahmudul; Shahrear, M. Khaled; Ikbal, Ashik (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Sino-nasal tumors, arising from the nasal cavity and sinuses, can be benign or malignant. Due to nonspecific symptoms and complex anatomy, diagnosis is often delayed. This study explores their prevalence, types, and distribution. Methods: This cross-sectional observational study was conducted at the ENT and head-neck surgery department, Rajshahi medical college hospital, Rajshahi, from June 2014 to November 2014. A total of 60 patients presenting with sinonasal tumors were selected as study subjects by purposive sampling technique. Data analysis was done by statistical package for social sciences (SPSS) version 20.0. A descriptive method was adopted. Results: This study on sino-nasal tumors found that 93.33% (56 out of 60) of the cases are benign, while only 6.67% (4 cases) are malignant. The maxillary antrum is the most affected site for malignancies (100%), followed by the nasal cavity (75%) and ethmoidal sinuses (25%). Among the malignant cases, 75% are classified as T4, indicating extensive disease. The most common benign tumors are haemangioma and rhinosporidiosis, each comprising 28.5% of benign cases. Squamous cell carcinoma (SCC) is the predominant malignant type, accounting for 75% of malignant tumors, highlighting the overall prevalence of benign lesions in the sinonasal region. Conclusions: This study highlights that benign sino-nasal tumors, especially haemangiomas and rhinosporidiosis, are more common, while SCC is the leading malignancy. Malignant cases often present late, mainly affect the maxillary antrum, and cause symptoms like nasal obstruction and facial pain.